Yuan and Roubles: Comparing Wage Determination in Urban China and Russia at the Beginning of the New Millennium - Björn Anders Gustafsson; Shi Li; Ludmila Nivorozhkina; Haiyuan Wan (Institute for the Study of Labor (IZA), 2014)
Earnings inequality and earnings determination in urban China 2002 and Russia 2003 are compared using samples covering large parts of the two countries. The results from estimated earnings functions are put in perspective of the outcome from a similar comparison made at the end of the 1980s. We confirm that earnings inequality has increased rapidly in both countries and is found to be similar across countries. As at the end of the 1980s, the gender wage gap is larger in Russia where earnings reach a maximum at a lower age than in China. The association between education and income in China has increased to become stronger than in Russia. The earnings penalty of being employed in the public service sector in Russia has increased while the publically employed in China enjoy a positive payoff of limited magnitude.
Keywords: J16; J31; J45; P23; 330; wages; wage inequality; gender wage gap; China; Russia